Reproductive health related complications of spinal cord injury among patients at a specialized center in Bangladesh - Nujhat, Mayesa; Kamal, S. M. Mustofa; Nazim, Anawarul Quader; Akter, Mst Fatema; Hossain, Mohammad Najmul; Uddin, Jasim; Fatima Camy, Kaniz; Tarin, Nure Taslima; Sarker Koushy, Eshika (International Journal of Research in Medical Sciences, 2023)
Background: Our objective was to find out the reproductive health related complications among spinal cord injury patients. Methods: A cross sectional study was conducted at the Center for the Rehabilitation of the Paralyzed (CRP) in Savar, Dhaka, Bangladesh from August 2017 to July 2018. A total of 289 patients, both indoor and outdoor, with spinal cord injury were randomly selected. The study aimed to examine reproductive health complications associated with spinal cord injury. Data was collected using a questionnaire and analyzed using SPSS version 20. Results: Among 220 (76.1%) were male and 69 (23.9%) were female. In 15-35 (68.1% and 91.2%), 47 (68.1%) participants had menstruation problem. 42.1% had autonomic dysreflexia and 57.9% had UTI as pregnancy related complications. In sexual activity 52% had difficulties having intercourse, 20% had difficulties to reach orgasm and 28% had dry sex. In male participants after SCI 70.5% had erection problem and 78.6% had ejaculation problem. Participants who had erection problem, most of their neurological level was thoracic level 84.51% and in case of ejaculation also their neurological level was thoracic level 81.50%. Conclusions: Awareness of sexuality and reproductive health after SCI has grown among healthcare professionals and individuals with spinal cord injuries. This recognition emphasizes the importance of open discussions, active listening, and education to enhance the quality of life for those affected by spinal cord injury.